2023
DOI: 10.1103/physrevapplied.19.034012
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity Control of the Topological-Insulator Surface Bi85Sb15(012) via Interfacial Engineering for Enhanced Spin-Orbit Torque

Abstract: Topological insulators demonstrate high charge-spin conversion efficiency due to their spin-momentum locking at the Dirac surface states. However, the surface states are sensitive to disruption caused by exchange coupling when interfaced with a ferromagnet. Here, we demonstrate the use of various nonmagnetic insertion layer materials, Ti, Cu, and Pt, at the Co/Bi-Sb(012) interface to preserve the topological surface state and promote spin-orbit-torque efficiency through the crystallinity control of Bi-Sb(012).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Smooth MBE films with good crystalline quality were obtained on GaMnAs-buffered GaAs (001) substrates . Moreover, the difficult integration of a buried MRAM stacking before TI growth motivated the search for different substrates and growth strategies. , In previous studies, we reported the 2D MBE growth of BiSb films with TSS on GaAs (111)­A and (001). , Room-temperature Hall measurements revealed a semiconducting behavior of the bulk, transiting to a metallic one below 100 K. Typical hole Hall mobilities at 20 K are 1430 and 7620 cm 2 /(V·s) for 450 nm and 1 μm thick films, respectively. , For the integration of such material in future low-energy consumption spintronic devices, two essential points need to be considered: the TI films’ uniformity and surface smoothness need to be optimized for magnetic material deposition and preserved topological surface states are required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smooth MBE films with good crystalline quality were obtained on GaMnAs-buffered GaAs (001) substrates . Moreover, the difficult integration of a buried MRAM stacking before TI growth motivated the search for different substrates and growth strategies. , In previous studies, we reported the 2D MBE growth of BiSb films with TSS on GaAs (111)­A and (001). , Room-temperature Hall measurements revealed a semiconducting behavior of the bulk, transiting to a metallic one below 100 K. Typical hole Hall mobilities at 20 K are 1430 and 7620 cm 2 /(V·s) for 450 nm and 1 μm thick films, respectively. , For the integration of such material in future low-energy consumption spintronic devices, two essential points need to be considered: the TI films’ uniformity and surface smoothness need to be optimized for magnetic material deposition and preserved topological surface states are required.…”
Section: Introductionmentioning
confidence: 99%
“…22 Moreover, the difficult integration of a buried MRAM stacking before TI growth motivated the search for different substrates and growth strategies. 23,24 In previous studies, we reported the 2D MBE growth of BiSb films with TSS on GaAs (111)A and (001). 25,26 Roomtemperature Hall measurements revealed a semiconducting behavior of the bulk, transiting to a metallic one below 100 K. Typical hole Hall mobilities at 20 K are 1430 and 7620 cm 2 / (V•s) for 450 nm and 1 μm thick films, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…BiSb typically crystallizes in a rhombohedral A7 crystal structure with a specific ordered arrangement of Bi and Sb atoms, as shown in Figure a. However, the low melting point of the BiSb alloy raises concerns about Bi/Sb diffusion and phase separation, which could compromise SOT efficiency during annealing and even room-temperature (RT) aging. , Also, the TSS of BiSb thin films was reported to be significantly affected by the selection of adjacent layers. , To date, it still remains a critical aspect requiring further investigation of the phenomenon of interdiffusion in the BiSb alloy with neighboring layers and interface chemistry to fully exploit the potential of BiSb-based heterostructures for spintronic applications.…”
Section: Introductionmentioning
confidence: 99%